2020
DOI: 10.1002/nop2.680
|View full text |Cite
|
Sign up to set email alerts
|

Stress and anxiety in nursing students between individual and peer simulations

Abstract: Background The use of high‐fidelity simulation practice as an educational tool is becoming increasingly prevalent in nursing education. Despite the learning effects of simulation practice, students have been shown to experience high levels of stress and anxiety during simulation. In recent years, peer learning has been defined as an acquisition of knowledge and skills through active support and support among equal or equal peers and has been shown to be an effective educational intervention for cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…We have not been able to identify studies exploring such associations. Nakayama et al (2020) explored factors that may possibly alleviate stress during simulations. They found that, in the face-to-face scene involving vital sign measurements, the presence of peers did not objectively alleviate stress (Nakayama et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We have not been able to identify studies exploring such associations. Nakayama et al (2020) explored factors that may possibly alleviate stress during simulations. They found that, in the face-to-face scene involving vital sign measurements, the presence of peers did not objectively alleviate stress (Nakayama et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, SBL is one of the techniques nurse educators might use to cope with conditions in the clinical environment that induce tension and distress among student nurses, such as fear of making errors, negative reactions to patient distress, and patient mortality. 5 Students gain psychomotor and technical abilities to enhance their cognitive capabilities across clinical conditions and make autonomous choices according to Oermann and Gaberson. 6 Nursing students who participate in SBL have more awareness and self-confidence as well as improved motivation, critical reasoning temperament, evaluation, and cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive learning effect of simulations, students experience high levels of stress and anxiety during simulations, negatively affecting their self-efficacy and learning results [ 24 ]. Using peer tutoring during simulations is effective in increasing learning efficacy by reducing tutees' anxiety [ 25 ]. In the current educational environment, where the use of simulations is increasing as an alternative to the unpredictable clinical practicum [ 26 ], the use of peer tutoring should be actively considered to provide reliable and effective simulations for neonatal nursing to students.…”
Section: Discussionmentioning
confidence: 99%